Analysis of demand for food commodities and its impact on the povert - Jumadil Saputra, Elda Elnovita, Abd. Jamal, Chenny Seftarita, (Opción, 2019)
This study is written to investigate the influence of price,income and demographic variables such as residential area andnumber of household members towards the demand for foodcommodities as sources of poverty in Aceh using the Almost IdealDemand System (AIDS). The result of data analysis shows that pricesand income have a significant effect on the demand for foodcommodities among poor families in Aceh. In conclusion, the sociodemographiccharacteristics showed that the demand for poorhouseholds in particular food commodities in an urban area is lowerthan in a rural area